2003
DOI: 10.1111/j.1601-1546.2003.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent, recurrent, and acquired infection of the root canal system post‐treatment

Abstract: Apical periodontitis is an inflammatory process in the periradicular tissues caused by microorganisms in the necrotic root canal. Accordingly, to achieve healing of apical periodontitis, the main goal of the treatment must be elimination of the infection and prevention of re‐infection. As shown by recent epidemiological studies in several countries around the world, post‐treatment endodontic disease is a far too common finding. To understand the reasons for survival of resistant bacteria in the filled root can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
136
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(152 citation statements)
references
References 167 publications
(262 reference statements)
5
136
0
11
Order By: Relevance
“…16 Both in vitro and in vivo observations show that bacterial penetration into dentinal tubules occurs as a random process, with bacterial colonies seen as sporadic, dense accumulations of cells (rather than as a continuous film), extending out from the main canal towards the periphery. 17 The reported frequency of dentinal tubule invasion in necrotic, infected teeth varies between 50 and 90 per cent. 17 When a root canal infection develops, the predentine is readily infected but the calcified dentine is less readily infected.…”
Section: Microbial Invasion Of Dentinementioning
confidence: 99%
See 1 more Smart Citation
“…16 Both in vitro and in vivo observations show that bacterial penetration into dentinal tubules occurs as a random process, with bacterial colonies seen as sporadic, dense accumulations of cells (rather than as a continuous film), extending out from the main canal towards the periphery. 17 The reported frequency of dentinal tubule invasion in necrotic, infected teeth varies between 50 and 90 per cent. 17 When a root canal infection develops, the predentine is readily infected but the calcified dentine is less readily infected.…”
Section: Microbial Invasion Of Dentinementioning
confidence: 99%
“…17 The reported frequency of dentinal tubule invasion in necrotic, infected teeth varies between 50 and 90 per cent. 17 When a root canal infection develops, the predentine is readily infected but the calcified dentine is less readily infected. Bacterial species that penetrate the dentine are dominated by Gram-positive rods (68 per cent) and cocci (27 per cent).…”
Section: Microbial Invasion Of Dentinementioning
confidence: 99%
“…Then, all the endodontic procedures are addressed to create and maintain the aseptic conditions for root canal filling 1 . The persistence of microorganisms is closely linked to the failures of endodontic treatments, and it often occurs due to failures on the root canal preparation, use of instruments and/or materials contaminated and infiltration of bacteria through the saliva 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Control of periapical infection is necessary to prevent the infection spreading into the underlying permanent tooth bud which lies in close proximity to the wide furcated roots of the deciduous teeth. 5 When failure of endodontic treatment occurs due to persistent bacterial infection in the root canal system, it is called as secondary infection. 6 The bacteria associated with periapical infection in primary teeth is polymicrobial in nature with a combination of Grampositive, Gram-negative aerobic and anaerobic organisms inhabiting the root canals, but studies have reported the maximum predominance of anaerobic microorganisms in the infected root canals.…”
Section: Introductionmentioning
confidence: 99%